Non-cardiac, non-oesophageal chest pain: the relevance of psychological factors. Issue 1 (1st July 1998) - Ho, K Y; Kang, J Y; Yeo, B; Ng, W L
Abstract : Background —No cause has been determined for chest pain that is neither cardiac nor oesophageal in origin. Aims —To compare the prevalence of lifetime psychiatric disorders and current psychological distress in three consecutive series of patients with chronic chest or abdominal pain. Patients —Thirty nine patients with non-cardiac chest pain and no abnormality on oesophagogastroduodenoscopy, oesophageal manometry, and 24 hour pH monitoring; 22 patients with non-cardiac chest pain having endoscopic abnormality, oesophageal dysmotility, and/or pathological reflux; and 36 patients with biliary colic. Methods —The Diagnostic Interview Schedule and the 28 item General Health Questionnaire were administered to all patients. Results —Patients with non-cardiac chest pain and no upper gastrointestinal disease had a higher proportion of panic disorder (15%), obsessive-compulsive disorder (21%), and major depressive episodes (28%) than patients with gallstone disease (0%, p<0.02; 3%, p<0.02; and 8%, p<0.05, respectively). In contrast, there were no differences between patients with non-cardiac chest pain and upper gastrointestinal disease and patients with gallstone disease in any of the DSM-111 defined lifetime psychiatric diagnoses. Using the General Health Questionnaire, 49% of patients with non-cardiac chest pain without upper gastrointestinal disease scored above the cut off point (that is, more than 4), which was considered indicative of non-psychotic psychiatric disturbance, whereas only 14% of patients with gallstones did so (p<0.005). The proportions of such cases were however similar between patients with non-cardiac chest pain and upper gastrointestinal disease (27%) and patients with gallstones. Conclusions —Psychological factors may play a role in the pathogenesis of chest pain that is neither cardiac nor oesophagogastric in origin.